The Theme of Loyalty and Betrayal in A. S. Pushkin's Novel "Eugene Onegin" (Zien Journal of Social Sciences and Humanities, 2025)
This article examines the theme of loyalty and infidelity in A.S. Pushkin's novel "Eugene Onegin." The main characters - Tatiana Larina, Eugene Onegin, Vladimir Lensky, and Olga Larina - are analyzed in terms of their devotion to feelings, ideals, and moral principles. Special attention is paid to the contrast between Tatiana's faithfulness and Onegin's frivolous attitude, as well as the tragic consequences of betrayal and disloyalty